1983
DOI: 10.3168/jds.s0022-0302(83)81910-9
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Traits of Holsteins and Jerseys. Effects of Age, Milk Yield, and Clinical Abnormalities on Involution of Cervix and Uterus, Ovulation, Estrous Cycles, Detection of Estrus, Conception Rate, and Days Open

Abstract: Two hundred and twelve Holstein and Jersey cows were in a study to determine factors that affected reproductive traits. First ovulation occurred about 3 wk postpartum, and interval to first ovulation was greater in cows that had clinical abnormalities postpartum than in normal cows. Jerseys producing more milk ovulated sooner postpartum than lower producing herdmates. Involution of cervix and uterus occurred later postpartum in cows that had clinical problems postpartum. Involution of genital tract occurred la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
157
5
19

Year Published

2003
2003
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 334 publications
(193 citation statements)
references
References 29 publications
12
157
5
19
Order By: Relevance
“…Opsomer et al (1998) observed a considerably later first ovulation in first parity compared with earlier studies (e.g. Fonseca et al, 1983). An increase of atypical patterns in milk progesterone profiles has also been observed by Royal et al (2000) comparing data from 1975 to 1982 with those from more recent years (1995)(1996)(1997)(1998).…”
Section: Introductioncontrasting
confidence: 42%
“…Opsomer et al (1998) observed a considerably later first ovulation in first parity compared with earlier studies (e.g. Fonseca et al, 1983). An increase of atypical patterns in milk progesterone profiles has also been observed by Royal et al (2000) comparing data from 1975 to 1982 with those from more recent years (1995)(1996)(1997)(1998).…”
Section: Introductioncontrasting
confidence: 42%
“…In addition, concentrations of P4 12 days before first AI had a positive relationship with conception rate at first AI in lactating Holstein and Jersey dairy cattle (Fonseca et al, 1983). Similarly, concentrations of P4 on the day of PGF2α-induced luteolysis had a positive linear correlation with subsequent fertility (Diskin et al, 2006).…”
Section: Fertility In Dairy Cowsmentioning
confidence: 85%
“…Although delayed first ovulation is clearly related to body condition score at calving and energy balance of early lactation, it is not as clearly related to milk production. Depending on the experiment but not on herd yield, greater Review: nutritional sub-fertility in the dairy cow milk yield increased the delay to first ovulation and/or to the day of commencement of luteal activity (C-LA) (Petersson et al, 2006), decreased it (Fonseca et al, 1983;Garbarino et al, 2004) or had no effect (Staples et al, 1990;Darwash et al, 1997;Gumen et al, 2005;Lopez et al, 2005;Pedernera et al, 2008). The effect of milk yield may also be approached by breed differences.…”
Section: Milk Production and Reproductive Performancementioning
confidence: 99%
“…The effect of milk yield may also be approached by breed differences. There are significant differences between breeds in the distribution of the beginning of corpus luteum activity (Fonseca et al, 1983;Disenhaus et al, 2009). Compared with other breeds, a higher proportion of Holstein cows have a very short delay in C-LA (,20 days postpartum (pp)) or a very long delay in C-LA (.80 days pp), leading to discrepancies from the average C-LA value.…”
Section: Milk Production and Reproductive Performancementioning
confidence: 99%